Tachycardia–Desaturation Episodes in Neonatal Intensive Care Unit Patients with and without Bronchopulmonary Dysplasia - Nagraj, V Peter; Howard, Paige; Fairchild, Karen D.; Sullivan, Brynne A. (American Journal of Perinatology, 2024)
Much attention has been paid to measuring physiological episodes of bradycardia–oxygen desaturation (BDs) in the neonatal intensive care unit (NICU). NICU patients also have spells of tachycardia–desaturation (TDs), but these have not been well-characterized. We hypothesized that TDs would be more common among infants with bronchopulmonary dysplasia (BPD). We aimed to quantify daily TDs compared to BDs in NICU patients across a range of gestational and postmenstrual ages (GA and PMA) and determine whether TDs are associated with BPD.We analyzed every 2-second heart rate (HR) and peripheral saturation of oxygen (SpO2) throughout the NICU stay of all infants with 24 to 39 weeks GA admitted to a single, level IV NICU from 2012 to 2015. BDs were defined in our prior work (HR <100 bpm for ≥4 seconds with concurrent SpO2 <80% for ≥10 seconds) and TDs as a 20% increase in HR from the previous 2-hour mean baseline and concurrent SpO2 <80% for ≥10 seconds. We calculated the median daily BDs and TDs across a range of GAs and PMAs. For infants ≤32 weeks GA, we compared TDs for those with and without BPD at 36 weeks PMA and discharge on supplemental oxygen.We analyzed 782,424 hours of HR and SpO2 data from 1,718 neonates, with a median of 271 hours analyzed per infant. TDs frequency increased with increasing PMA across all GAs. BDs occurred most frequently in infants <29 weeks GA and decreased as infants approached term equivalent age. For infants with ≤32 weeks GA, one or more TD per day from 33 to 35 weeks PMA was associated with BPD and home oxygen.Episodes of TD at the thresholds defined in this analysis occurred more frequently at later PMA and were more common in infants with BPD and those requiring home oxygen.
Keywords: neonates; desaturation; tachycardia; bronchopulmonary dysplasia